AN ASSESSMENT OF RADIO TALK SHOW PRESENTERS HANDLING OF CONTENT AGAINST MEDIA COUNCIL OF KENYA'S LAID DOWN PROFESSIONAL AND ETHICAL STANDARDS: A STUDY OF SELECTED FM RADIO STATIONS - Okumbe, Margaret Ayuma; Peel, Prof. Clayton; Adagala, Nancy (International Journal of Communication and Public Relation, 2017)
Purpose: The study aimed at interrogating radio talk show content, particularly the concern of whether the presenters adhered to professional standards as outlined in the Code of Conduct for Practice of Journalism in Kenya. Materials and methods: The three study sites were local FM radio stations - Radio Citizen, Radio Jambo, and Radio Maisha. Using a 2014 Media Council of Kenya study of radio talk shows in Kenya as a background,the thesis placed more emphasis on the radio presenters and their content. The study applied Social Responsibility Theory which posits that media should be more responsible and accountable to the society. The study employed a descriptive survey using qualitative and quantitative approaches. In this study, four presenters, two key personnel from the Media Council of Kenya were interviewedas well as a sample of their radio talk show content. Results: This study noted that the regulatory bodies such as the MCK and theCommunication Authorityof Kenyawere leading efforts to regulate content in the interests of decency. The limitations of the MCKas a media regulatory body were lack of capacity to monitor radio stations, resulting in poorenforcement of the journalists' code of ethics. Recommendations: The study recommends that the CA and the MCK come to a consensus in regard to the regulation of media practice in Kenya.The two statutory bodies need to be clear on the distinction between their roles, and to involve other stakeholders in addressing matters of non-conformityto regulations by media houses.Moreover,the MCK needs to prepare separate codes for broadcast media regulations (ACMA, 2011).